Impacts of delayed addition of N-rich and acidic substrates on nitrogen loss and compost quality during pig manure composting. (February 2018) - Jiang, Jishao; Kang, Kang; Chen, Dan; Liu, Ningning
Highlights: N-rich and acidic substrates was added at different times during composting. Delayed addition of N-rich and acidic substrates reduced nitrogen loss. Delayed addition of N-rich and acidic substrates improved compost quality. Abstract: Delayed addition of Nitrogen (N)-rich and acidic substrates was investigated to evaluate its effects on N loss and compost quality during the composting process. Three different delayed adding methods of N-rich (pig manure) and acidic substrates (phosphate fertilizer and rotten apples) were tested during the pig manure and wheat straw is composting. The results showed that delayed addition of pig manure and acidic materials led two temperature peaks, and the durations of two separate thermophilic phase were closely related to the amount of pig manure. Delayed addition reduced total N loss by up to 14% when using superphosphate as acidic substrates, and by up to 12% when using rotten apples as acidic substrates, which is mainly due to the decreased NH3 emissions. At the end of composting, delayed the addition of pig manure caused a significant increase in the HS (humus substance) content, and the highest HS content was observed when 70% of the pig manure was applied at day 0 and the remaining 30% was applied on day 27. In the final compost, the GI in all treatments almost reached the maturity requirement by exceeding 80%. The results suggest that delayed addition of animal manure and acidic substrates could prevent the N loss during composting and improve the compost quality.